Experimental pharmacological approaches to reverse impaired awareness of hypoglycemia-a review - Hiba Z. Hashmi; Ameer Khowaja; Amir Moheet (Frontiers Media S.A., 2024)
The colossal global burden of diabetes management is compounded by the serious complication of hypoglycemia. Protective physiologic hormonal and neurogenic counterregulatory responses to hypoglycemia are essential to preserve glucose homeostasis and avert serious morbidity. With recurrent exposure to hypoglycemic episodes over time, these counterregulatory responses to hypoglycemia can diminish, resulting in an impaired awareness of hypoglycemia (IAH). IAH is characterized by sudden neuroglycopenia rather than preceding cautionary autonomic symptoms. IAH increases the risk of subsequent sudden and severe hypoglycemic episodes in patients with diabetes. The postulated causative mechanisms behind IAH are complex and varied. It is therefore challenging to identify a single effective therapeutic strategy. In this review, we closely examine the efficacy and feasibility of a myriad of pharmaceutical interventions in preventing and treating IAH as described in clinical and preclinical studies. Pharmaceutical agents outlined include N-acetyl cysteine, GABA A receptor blockers, opioid receptor antagonists, AMP activated protein kinase agonists, potassium channel openers, dehydroepiandrosterone, metoclopramide, antiadrenergic agents, antidiabetic agents and glucagon.